Financial Education in Teacher Training: a healthy discussion at EBRAPEM (Research, Society and Development, 2022)
The inclusion of teachers in basic and financial education implies, among many responsibilities, the development of activities that cover various themes, including the knowledge obtained during initial formation, and others that are necessary and can contribute to their school practice, also with the student's cognitive development. Therefore, teachers need to appropriate basic concepts related to the subject and, thus, develop activities that help students using this knowledge with the necessary criticality. Thereby, this work aims analyzing the scientific production arising from debates on financial education and teachers formation occurred at BMGSME in the last editions (XX to XXIV). In this sense, a mapping of published articles from 2016 to 2020 was carried out, containing this thematic focus, in which 36 productions were raised through inclusion and exclusion criteria, was possible to identify the six that directly addressed financial education. Through the themes categorization, it was decided to classify them into 3 categories: "Aimed at initial training", "The use of digital technologies as an aid for teaching financial education", and "Financial education in the conception of students to aid in decision making". The results revealed that it is necessary especially in North and Midwest regions, to have more discussions with teachers who work with financial education, with students and mainly with those of initial formation.